Habitual Light-intensity Physical Activity and ASC Methylation in a Middle-aged Population - Nishida, Yuichiro; Hara, Megumi; Higaki, Yasuki; Taguchi, Naoto; Nakamura, Kazuyo; Nanri, Hinako; Horita, Mikako; Shimanoe, Chisato; Yasukata, Jun; Miyoshi, Nobuyuki; Yamada, Yosuke; Higashimoto, Ken; Soejima, Hidenobu; Tanaka, Keitaro (International Journal of Sports Medicine, 2019)
Apoptosis-associated, speck-like protein containing a caspase recruitment domain (ASC) plays an important role in inflammatory cytokine synthesis in peripheral blood mononuclear cells (PBMCs), and the expression of ASC is suppressed by increased methylation of its CpG sites. The current study investigated the longitudinal association of replacing sedentary time with light-intensity physical activity (LPA) or moderate to vigorous-intensity physical activity (MVPA) on the ASC methylation in middle-aged people. We investigated 1 238 individuals who participated in baseline and 5-year follow-up surveys of a population-based cohort study. Sedentary, LPA and MVPA time were objectively measured using accelerometers. ASC methylation in PBMCs was measured by pyrosequencing. Using a multiple linear regression and employing an isotemporal substitution model, the longitudinal associations of changes in the sedentary time, LPA and MVPA on the changes in the ASC methylation were analyzed after adjusting for potential confounders. Substituting 60 min per day of LPA for sedentary time was associated with 1.17 times (95% confidence interval 1.07, 1.27) higher ASC methylation levels (mean of 7 CpG sites, P<0.001). However, such effects were not seen for MVPA. These results suggest that substituting LPA for sedentary time may be linked with increased (favorable) ASC methylation as a potential biomarker of systemic inflammation.
Keywords: DNA methylation; exercise; inflammation; isotemporal substitution